Acceptability and Feasibility of Integrating Point-of-Care Diagnostic Testing of Sexually Transmitted Infections into a South African Antenatal Care Program for HIV-Infected Pregnant Women. (9th May 2018) - Morikawa, E.; Mudau, M.; Olivier, D.; de Vos, L.; Joseph Davey, D.; Price, C.; McIntyre, J. A.; Peters, R. P.; Klausner, J. D.; Medina-Marino, A.
Abstract : Background . Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), and Trichomonas vaginalis (TV) infections may increase the risk of vertical transmission of the human immunodeficiency virus (HIV). In resource-limited settings, symptomatic screening, and syndromic management of sexually transmitted infections (STIs) during pregnancy continue to be the standard of care. In the absence of diagnostic testing, asymptomatic infections in pregnant women go untreated. Objective . To describe the acceptability and feasibility of integrating diagnostic STI screening into first antenatal care visits for HIV-infected pregnant women. Methods . HIV-infected pregnant women were recruited during their first antenatal care visit from three antenatal care clinics in Tshwane District, South Africa, between June 2016 and October 2017. Self-collected vaginal swabs were used to screen for CT, NG, and TV with a diagnostic point-of-care (POC) nucleic acid amplification test. Those with STIs were provided treatment per South African national guidelines. Results . Of 442 eligible women, 430 (97.3%) agreed to participate and were tested. Of those with a positive STI test result (n = 173; 40.2%), 159 (91.9%) received same-day results and treatment; 100% of STI-infected women were treated within seven days. Conclusions . Integration of POC diagnostic STI screening into first-visit antenatal care services was feasible and highly acceptable for HIV-infected pregnant women.